A Bifunctional Nanosilver-Reduced Graphene Oxide Nanocomposite for Label-Free Electrochemical Immunosensing - Chanarsa, Supakeit; Jakmunee, Jaroon; Ounnunkad, Kontad (Frontiers in Chemistry, 2021)
A bifunctional material based on silver nanoparticles (AgNPs)-reduced graphene oxides (rGO) composite for both electrode modification and signal generation is successfully synthesized for use in construction of label-free electrochemical immunosensor. An AgNPs/rGO nanocomposite is prepared by a one-pot wet chemical process. The AgNPs/rGO composite dispersion is simply casted on the screen-printed carbon electrode (SPCE) to fabricate the electrochemical immunosensor. It possesses a sufficient conductivity/electroreactivity and improves the electrode reactivity of SPCE. Moreover, the material can generate the analytical response due to formation of immunocomplexes for detection of human immunoglobulin G (IgG), a model biomarker. Based on electrochemical stripping of AgNPs, the material reveals the signal amplification without external redox molecules/probes. Under the optimized condition, the square wave voltammetric peak current is responded to the logarithm of IgG concentration in two wide linear ranges from 1.0 to 50 pg.mL-1 and 0.050 to 50 ng.mL-1 and a limit of detection (LOD) is estimated to be 0.86 pg.mL-1. Our proposed immunosensor displays satisfactory sensitivity and selectivity. Importantly, the detection of IgG in the human serum using such sensor shows satisfactory accuracy, which possesses a huge potential for further development in clinical diagnosis.